Pengaruh Hypnobirthing Dan Murrotal Terhadap Intensitas Nyeri Persalinan Kala I Fase Aktif Pada Primigravida - Hesti Ratna Sari; Suhendar Sulaiman; Idriani Idriani (Indonesian National Nurses Association (INNA) of Central Java, 2020)
Labor pain is a unique and subjective experience, where each individual has a different response. Non-pharmacological pain management methods include pain management, namely hypnobirthing and murrotal. The purpose of this study was to determine the effect of hypnobirthing and murrotal therapy on the intensity of active fisrt stage of labor pain in primigravida at Singadaru and Banten Girang Health Center, Serang City, Banten Province. The research design used a quasy experimental approach without control group. The total sample in this study were 25 women giving birth. The data collection tool used was the pain scale VAS & NRS. Data analysis used descriptive analysis, using the Wilcoxon statistical test to compare data before and after the intervention. The results showed that there were differences in the average pain intensity before and after hypnobirthing intervention was given (p value = 0.010, ∆ = 1.5). There is a difference in the mean intensity of labor pain in primigravida before and after given murrotal intervention (p value = 0.014, ∆ = 1.5). The difference in the average intensity of labor pain before and after giving hypnobirthing and murrotal intervention (p value = 0.006, ∆ = 2). The conclusion from the results of the three interventions given were all significant, but the difference between pain intensity and high value was found in murrotal and hypnobithing interventions. The combination of hypnobirthing and murrotal recommendations can be used as an alternative to distract labor pain, and increased belief in god